Farm household typologies and mechanization patterns in Nepal Terai: Descriptive analysis of the Nepal living standards survey - Takeshima, Hiroyuki; Adhikari, Rajendra Prasad; Poudel, Mahendra Nath; Kumar, Anjani (International Food Policy Research Institute, 2015)
Although Nepal formulated an agricultural mechanization promotion policy in 2014, there is still much to learn about tailoring mechanization policies to different types of farm households. The Terai belt in Nepal has seen steady growth in tractor use in the past 20 years, but heterogeneity exists among farm households. In this study, we use Nepal Living Standards Survey data to analyze such heterogeneity from a farm typology perspective. We characterize farm households based on use of external agricultural inputs, including tractors. Growth of tractor use in the Terai is associated with input use intensification per cultivated area, rather than significant expansion of cultivated area. Tractor use in the Terai appears to have grown as part of such land-saving intensification, although larger farm owners do hire in more tractors. We find that differences in household income portfolios are not straightforward between tractor renters and nonrenters, without clear differences in specialization of economic activities as well as farming systems. Tractor renters consist of various types, including the power-intensive mechanizer, intensive labor hirer, and fertilizer-based intensifier. Such heterogeneity recommends the use of tailored mechanization policy options.